ANALISIS YURIDIS PRAKTIK JUAL BELI JABATAN OLEH BUPATI PATI SEBAGAI BENTUK PENYALAHGUNAAN WEWENANG DALAM PERSPEKTIF UU NO 30 TAHUN 2014 - Auliya Putri Riski; Nur Fadilla; Mery Fernandes Sinaga; Rimma Anisa Siagian; Roslin Naiborhu; Taufiq Ramadhan Ramadhan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to juridically analyze the practice of position trading carried out by the Regent of Pati as a form of abuse of authority from the perspective of Law Number 30 of 2014 concerning Government Administration. This issue is motivated by the increasing occurrence of authority abuse by public officials in the appointment of Civil Servant positions, which are no longer based on the merit system but rather on personal interests or certain rewards. Such practices not only undermine the principle of the rule of law but also contradict the General Principles of Good Governance (AUPB) and the principles of good governance.This research uses a qualitative method with a normative juridical approach, through analysis of laws and regulations, doctrines of state administrative law, and relevant scientific literature. The results of the study indicate that the authority of the Regent in appointing positions derives from attribution and delegation limited by Law Number 23 of 2014 concerning Regional Government, Law Number 20 of 2023 concerning the State Civil Apparatus, and Law Number 30 of 2014 concerning Government Administration.The practice of position trading fulfills the elements of abuse of authority (detournement de pouvoir) because the authority is exercised not in accordance with its intended purpose, thereby violating the principles of legality, legal certainty, impartiality, and the principle of not abusing authority as regulated in Article 17 and Article 18 of Law Number 30 of 2014. Furthermore, the abuse of authority committed by the Regent of Pati also constitutes a criminal act of corruption in accordance with Law Number 20 of 2001.The legal implications of such practices not only result in administrative defects in appointment decisions that can be annulled through the State Administrative Court but also constitute a criminal offense of corruption, as the authority is used for personal gain rather than for public interest.